2016
DOI: 10.5005/jp-journals-10024-1845
|View full text |Cite
|
Sign up to set email alerts
|

Mini-implants for Orthodontic Anchorage: Surface Analysis after Redrilling and Sterilization – An in vitro Study

Abstract: Objective: This study aimed to investigate, in vitro, possible alterations on mini-implants surface after retrieval and if the cleaning process and sterilization can predispose damages. Materials and methods:Two commercial mini-implants were tested for deformations after drilling and removing in artificial bone four times. Samples were analyzed by scanning electron microscopy, and surface alterations verified through thread and pitches deformation. To alterations caused by insertion/removal and the cleaning pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The images were obtained with secondary electron detector, increasing from 200× to 2000×, 20 kV, and 0.8 μA. 21…”
Section: Analysis Of the Miniscrews Surfaces Under Semmentioning
confidence: 99%
“…The images were obtained with secondary electron detector, increasing from 200× to 2000×, 20 kV, and 0.8 μA. 21…”
Section: Analysis Of the Miniscrews Surfaces Under Semmentioning
confidence: 99%
“…The aforementioned situations are all related with the reuse of microimplants, including immediate relocation and postponed relocation. However, it remains controversial whether the reuse of microimplants is sensible and feasible (Mattos et al, 2010;Chung et al, 2014;Estelita et al, 2014;Iijima et al, 2015;Noorollahian et al, 2015;Gross et al, 2016). In previous studies, some researchers described their recycling protocols and reported that their methods had no significant negative effects on mechanical strength (Estelita et al, 2014;Noorollahian et al, 2015;Gross et al, 2016), while others did not recommend the reuse of retrieved microimplants because of their altered surface characteristics and changed mechanical properties (Mattos et al, 2010;Chung et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A thorough understanding of biomechanical principles involved in the application of micro-implants should be known, and the complete assessment of anchorage should be evaluated at the start of the treatment. [ 10 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Immediate loading in clinical practice could reduce osteointegration and thus leads to soft tissues not enveloping the mini-screw surfaces. [ 9 10 ] Manufactures usually supply information on outer diameter, length, and chemical composition. Depth, pitch, and lead angle of the thread and surface characteristics are rarely provided.…”
Section: Introductionmentioning
confidence: 99%